The idea of Europe and the origins of the American revolution - Robinson, Daniel 1990- (Oxford University Press, 2020)
In this path-breaking history of early America, the imperial crisis, and the American Revolution, D.H. Robinson traces the formative impact of ideas about Europe and Europeanness on British-American politics and identity, touching on everything from international relations and nationalism, to news media and poetry